DAMPAK KERUSUHAN 15 MEI 1998 TERHADAP KEHIDUPAN MASYARAKAT DI DESA KARANG ASIH - Hendri Wianingsih; Maskun Maskun; Syaiful M (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2013)
Impact Against Riots May 15 1998 in the village of Karang Community Life Asih North Cikarang Bekasi District. In 1998 There were riotsinthe village of Karang Asih Cikarang precisely in new markets, while the perpetrators were from out side the are apast the village of Karang Asih of unknow norigin. They do the looting and arsonin new markets Cikarang. This study aims to determine the impact of the riots of 199 Socio-Economic Society In Karang Mercy. The method used is the historical method, and using the techniques of data collection through observation, and interviews, and analyzing the data with qualitative data analysis techniques.  Results of this study in dicate that the Karang village traders Asih ladder can notsend their children to higher educationdue to costconstraints. After the riots they work as a motorcycle, the driver, rickshaw and factory workers. Income of each family experienced ups and downs over the development of the market. Availability of supply of essential goods can besaid to befulfilled, but the value of a high selling price. It can be concluded that the socio-economic impacts tha occur include the impact of education level, income, level of income and subsistence. Keywords: Impact, Riots, Society